Improvement of Soybean Oil Solvent Extraction through Enzymatic Pretreatment - F. V. Grasso; P. A. Montoya; C. C. Camusso; B. G. Maroto (International Journal of Agronomy)
The purpose of this study is to evaluate multienzyme hydrolysis as a pretreatment option to improve soybean oil solvent extraction and its eventual adaptation to conventional processes. Enzymatic action causes the degradation of the cell structures that contain oil. Improvements in terms of extraction, yield, and extraction rate are expected to be achieved. Soybean flakes and collets were used as materials and hexane was used as a solvent. Temperature, pH, and incubation time were optimized and diffusion coefficients were estimated for each solid. Extractions were carried out in a column, oil content was determined according to time, and a mathematical model was developed to describe the system. The optimum conditions obtained were pH 5.4, 38°C, and 9.7 h, and pH 5.8, 44°C, and 5.8𲀉h of treatment for flakes and collets, respectively. Hydrolyzed solids exhibited a higher yield. Diffusion coefficients were estimated between 10-11 and 10-10. The highest diffusion coefficient was obtained for hydrolyzed collets. 0.73 g oil/mL and 0.7 g oil/mL were obtained at 240 s in a column for collets and flakes, respectively. Hydrolyzed solids exhibited a higher yield. The enzymatic incubation accelerates the extraction rate and allows for higher yield. The proposed model proved to be appropriate.